Pesantren Teachers‘ Commitment from the Perspective of Local Wisdom: Sustainable Strategies for Curriculum Reinforcement - Rasyidin Rasyidin; Fauzan Ahmad Siregar; Abdullah Sani Ritonga (Institut Agama Islam Negeri Lhokseumawe, 2025)
This study aims pesantren teachers' commitment from the perspective of local wisdom as a foundation for sustainable curriculum reinforcement. Using a qualitative descriptive survey. The study reveals that the curriculum at Pesantren Ar Raudlatul Hasanah integrates five key orientations: holistic development, skill enhancement, incorporation of local wisdom, character building, and field project engagement. These elements manifest in both the official and hidden curricula and are delivered through direct instruction. Teacher commitment in this pesantren is categorized into three types: affective commitment, reflecting emotional connection; normative commitment, showing pedagogical dedication; and continuance commitment, prioritizing the pesantren's well-being. These overlapping commitments contribute significantly to the effectiveness of the educational program. Moreover, strong relationships among teachers foster a supportive, participatory environment, enhanced by social support, a sense of belonging, professional development opportunities, and a mentorship system. This supportive community strengthens teachers' enthusiasm and dedication, suggesting that fostering collaborative group activities can sustainably reinforce curriculum quality and educational outcomes in pesantren institutions.